Pengaruh Kepemimpinan Konsultatif Dan Kompensasi Terhadap Komitmen Organisasi - Titi Titi; Vicky Achmad Zulfikar (Majalah Bisnis & IPTEK, 2019)
This study aims to determine the effect of consultative leadership and compensation on organizational commitment. The important role of consultative leadership can be divided into three aspects namely conformity of goals, level of work and LMX (strong exchange relations). While compensation is divided into two parts, namely financial compensation and non-financial compensation. The research method used is a verification method. The sample used is an employee used car showroom in the city of Bandung. Data analysis techniques using path analysis. The results of the study prove that there is an influence of consultative leadership and compensation on organizational commitment of 66.5%.